Harmonic, wavelet and p-adic analysis - Chuong, N. M. (Nguyen Minh) (Singapore ; Hackensack, NJ : World Scientific, 2007)
The mutual influence between mathematics and science and technology is becoming more and more widespread with profound connections among them being discovered. In particular, important connections between harmonic analysis, wavelet analysis and p-adic analysis have been found recently. This volume reports these findings and guides the reader towards the latest areas for further research. It is divided into two parts: harmonic, wavelet and p-adic analysis and p-adic and stochastic analysis.
Preface; CONTENTS; Part A Wavelet and Harmonic Analysis; Chapter I Wavelet and Expectations; Chapter II Harmonic Analysis; Part B P-adic and Stochastic Analysis; Chapter III Over padic Field; Chapter IV Archimedean Stochastic Analysis.
Includes bibliographical references.
Print version record.
eBooks on EBSCOhost
Keywords: Harmonic analysis -- Congresses; p-adic analysis -- Congresses; Analyse harmonique -- Congrès.; Analyse p-adique -- Congrès.; MATHEMATICS -- Infinity; Harmonic analysis; p-adic analysis; Electronic books; Conference papers and proceedings